2019
DOI: 10.20950/1678-2305.2019.45.1.325
|View full text |Cite
|
Sign up to set email alerts
|

QUALIDADE DA CARNE E RESPOSTAS DE ESTRESSE EM Piaractus mesopotamicus APÓS EXPOSIÇÃO í­â‚¬ NÍVEIS SUBLETAIS DE AMÔNIA E SUBSEQUENTE RECUPERAÇÃO

Abstract: This study aimed to evaluate de effect of the exposure to sub-lethal levels of ammonia on blood parameters and flesh quality of juvenile pacu (Piaractus mesopotamicus), including assessment of such parameters post recovery in ammonia-free water. Juveniles (27.1 ± 5.4 g) were exposed to concentrations of ammonia at 0.0 (control); 0.5; and 1.0 mg N-NH3 L-1 for 10 days followed by the same period of recovery in ammonia-free water. On the 10th day post exposure and after a recovery period, samples of blood were ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
1
3
1
Order By: Relevance
“…The higher blood glucose levels in stressed fish are directly associated with increased carbohydrate metabolism (Lemos et al, 2018), which was an expected result in this study. Similar evidence has also been reported in different stressful situations for pacu in other studies (Copatti et al, 2019;Nitz et al, 2019;Pinto et al, 2019).…”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…The higher blood glucose levels in stressed fish are directly associated with increased carbohydrate metabolism (Lemos et al, 2018), which was an expected result in this study. Similar evidence has also been reported in different stressful situations for pacu in other studies (Copatti et al, 2019;Nitz et al, 2019;Pinto et al, 2019).…”
Section: Methodssupporting
confidence: 90%
“…In Brazil, it is part of a group known as round fish that represent the second largest group of farmed fish (Valenti et al, 2021). In addition, this species is resistant to low oxygen levels (Cunha Bastos et al, 2007; Nitz et al, 2020b) and tolerates medium and high ammonia levels (Nitz et al, 2019) and adverse conditions of acid and alkaline pH in water (Copatti et al, 2019; Pellegrin et al, 2020). Moreover, pacu are omnivorous and have a low‐protein diet based on vegetables, consequently reducing production costs (Urbinati et al, 2010; Valladão et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Datos morfométricos y resultados de la composición aproximada de cuatro especies de peces de agua dulce del Brasil de la familia Serrasalmidae. content was found in C. macropomum compared to P. mesopotamicus, and both fish species were reported with similar moisture content (Nitz et al, 2019;Silva et al, 2018;Sousa et al, 2019). In the present study, although no difference (p > 0.05) was observed in ash content among PM, CM and PC, a similarity (p > 0.05) in moisture, lipid, and protein contents was only observed between PC and CM.…”
Section: Proximate Compositioncontrasting
confidence: 45%
“…Considering fish farmed in Brazil, similar values of lipids were reported for Colossoma macropomum and Piaractus mesopotamicus X Colossoma macropomum (Castro et al, 2007;Silva et al, 2018;Sousa et al, 2019), while Piaractus mesopotamicus has been usually reported with higher lipid content than C. macropomum and P. mesopotamicus X C. macropomum (Andrade et al, 1995;Nitz et al, 2019). Moreover, some authors observed similar ash content between P. mesopotamicus and C. macropomum (Nitz et al, 2019;Sousa et al, 2019). On the other hand, higher protein Table 1.…”
Section: Proximate Compositionmentioning
confidence: 56%
“…In addition, pacu is an established aquaculture species with good potential for intensive aquaculture due to its hardiness including a high tolerance to low DO levels, different temperature ranges, as well as contrasting pH levels and high concentrations of ammonia. It also has high growth performance and produces fillets with excellent nutritional quality that are well‐accepted by the consumer market (Jomori, Carneiro, Malheiros, & Portella, 2003; Nitz et al., 2019; Pellegrin, Nitz, Maltez, Copatti, & Garcia, 2020; Pinto et al., 2019; Sampaio et al., 2008). In fish farms, it is also susceptible to hypoxia conditions due to high stocking density conditions (Bittencourt et al., 2010).…”
Section: Introductionmentioning
confidence: 99%